Synthesis and Characterization of Activated Carbon from Lignocellulosic Biomass: Oil Palm Empty Fruit Bunches and Mahogany Sawdust - Arundina, Ria Yolanda; Permana, Indri; Togatorop, Ester Rimma Suryani; Ismadi, Ismadi; Kusumah, Sukma Surya; Budiman, Ismail; Subyakto, Subyakto; Marlina, Resti (Universitas Negeri Semarang, 2021)
Lignocellulosic biomass is a biological residue from the agricultural or forestry industry which is composed of polymeric cellulose, hemicellulose, lignin, and other extractive components. One of the products in the utilization of lignocellulosic biomass waste is activated carbon products. In this study, two types of lignocellulosic biomass waste were used, namely Empty Palm Oil Bunches (OPEFB) and Mahogany Sawdust (MS) to be converted into activated carbon using the hydrothermal-pyrolysis method. Potassium hydroxide (KOH) was used as an activating agent at high concentrations (50% w/w) to improve the adsorption mechanism in activated carbon material. Proximate analysis was carried out to obtain information related to yield, moisture content, and ash content. In addition, activated carbon samples were characterized using FTIR, XRD, and FESEM to observe the chemical bonds, structure, and morphology of activated carbon, respectively. The proximate analysis showed that the activated carbon sample had met the SNI 63-3730-1995 standard for technical activated carbon on the parameters of water content and ash content, while the FTIR spectrum showed the mechanism of biomass conversion from raw materials to activated carbon on a chemical bond approach. Furthermore, the XRD graph shows a reduction in the crystal size of the material from raw material to activated carbon material. Finally, the FESEM image shows a significant increase in the quality and quantity of pores on the carbon material before and after activation.